2019
DOI: 10.1111/1758-2229.12764
|View full text |Cite
|
Sign up to set email alerts
|

In silicoprediction of the secretome from the invasive neurotoxic marine dinoflagellateAlexandrium catenella

Abstract: Summary Alexandrium catenella, a marine dinoflagellate responsible for harmful algal blooms (HABs), proliferates with greater frequency, distribution and intensity, in disturbed marine coastal ecosystems. The proteins secreted into seawater may play a crucial role in maintaining this dinoflagellate in these ecosystems, but this possibility has never been investigated before. In this study, the A. catenella secretome was predicted from its transcriptome by combining several bioinformatics tools. Our results pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…However, few studies have investigated the ability of A. pacificum to adapt to and/or tolerate disturbed environments such as metal-contaminated coastal ecosystems. In silico prediction of the A. pacificum secretome, outside specific conditions, has shown that proteins released in the extracellular medium are J o u r n a l P r e -p r o o f mainly enzymes (Chetouhi et al, 2019). Enzymatic activity of these secreted proteins could contribute to regulate the extracellular environment and be involved in some stress responses, which may help this dinoflagellate to develop in metal-contaminated conditions.…”
Section: Alexandrium Pacificummentioning
confidence: 99%
“…However, few studies have investigated the ability of A. pacificum to adapt to and/or tolerate disturbed environments such as metal-contaminated coastal ecosystems. In silico prediction of the A. pacificum secretome, outside specific conditions, has shown that proteins released in the extracellular medium are J o u r n a l P r e -p r o o f mainly enzymes (Chetouhi et al, 2019). Enzymatic activity of these secreted proteins could contribute to regulate the extracellular environment and be involved in some stress responses, which may help this dinoflagellate to develop in metal-contaminated conditions.…”
Section: Alexandrium Pacificummentioning
confidence: 99%
“…An ecotoxicoproteomic study on the Mediterranean strain (ACT03) of A. pacificum showed that single-stress by lead or zinc induced the down-regulation of many proteins constituting its soluble proteome, compensated by the up-regulation of some proteins like ATP-synthase able to contribute to an adaptive proteomic response in metal-contaminated ecosystems (Jean et al, 2017). Using an in silico approach, the secretome of A. pacificum has been predicted, showing that 47% of the secreted proteins are enzymes (peptidases) active in the extracellular medium during stress responses, Journal Pre-proof J o u r n a l P r e -p r o o f 5 which could help this dinoflagellate to develop in various environmental conditions, such as in metal-contaminated areas (Chetouhi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%